2018
DOI: 10.1016/j.biopsych.2018.01.026
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Alcohol Seeking in Mice Lacking Gpr88 Involves Dysfunctional Mesocorticolimbic Networks

Abstract: Gpr88 deletion disrupts executive, reward, and emotional networks in a configuration that reduces alcohol reward and promotes alcohol seeking and drinking. The functional connectivity signature is reminiscent of alterations observed in individuals at risk for AUD. The Gpr88 gene, therefore, may represent a vulnerability/resilience factor for AUD, and a potential drug target for AUD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 75 publications
4
66
0
Order By: Relevance
“…Because GPR88 KO mice showed enhanced motivation for alcohol drinking and seeking behaviors, 23 we sought to determine whether RTI-13951-33 would be effective in vivo to alter operant alcohol self-administration. Female Long Evans rats were trained to self-administer alcohol, as described in our recent publications (15% alcohol [v/v] + 2% [w/v] sucrose vs inactive lever).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because GPR88 KO mice showed enhanced motivation for alcohol drinking and seeking behaviors, 23 we sought to determine whether RTI-13951-33 would be effective in vivo to alter operant alcohol self-administration. Female Long Evans rats were trained to self-administer alcohol, as described in our recent publications (15% alcohol [v/v] + 2% [w/v] sucrose vs inactive lever).…”
Section: Resultsmentioning
confidence: 99%
“…1822 Interestingly, a recent GPR88 KO study demonstrated that the GPR88-deficient mice displayed enhanced voluntary alcohol drinking in both moderate and excessive drinking paradigms compared with wild-type (WT) mice. 23 No alterations in water intake, palatability, and alcohol metabolism were observed in these mice. 23 Moreover, mice lacking the GPR88 gene showed enhanced motivation for alcohol drinking and seeking behaviors using operant self-administration.…”
Section: Introductionmentioning
confidence: 82%
“…Bmal1SKO and Per2SKO mice and their respective HET counterparts have only one functional copy of Gpr88 in MSNs since one copy is modified to drive Cre and GFP expression. Complete deletion of Gpr88 has been shown to augment alcohol intake in male mice [47,48], raising the possibility that the changes in alcohol consumption seen in striatal Bmal1SKO and striatal Per2SKO were due, at least in part, to a contributory effect of Gpr88 monoallelic expression. To study this possibility, we compared alcohol intake and preference between Gpr88+/+ mice (males, n = 7; females, n = 10) and Gpr88Cre/+ mice (males, n = 7; females, n = 12).…”
Section: Gpr88 Monoallelic Expression Does Not Affect Alcohol Intakementioning
confidence: 99%
“…Importantly, several of these GPCRs modulate behaviors related to drugs of abuse. For example, the receptor for melanin-concentrating hormone (MCHR1) modulates responses to psychostimulants, and the orphan GPCR, GPR88, modulates alcohol intake [16,[19][20][21][22]. To date, however, the role or necessity of neuronal cilia in responses to drugs of abuse is essentially unknown.…”
Section: Introductionmentioning
confidence: 99%